LDPC Code-Based Distributed Source Coding With an Efficient Message Passing Mechanism for the Compression of Correlated Image Sources - Mo, Hong; Chen, Jianhua (IEEE transactions on image processing, 2024)
Different from traditional source coding techniques, distributed source coding (DSC) techniques rely on independent encoding at the encoding end but joint decoding at the decoding end to compress image sources which exhibit correlation. Channel code-based DSC techniques compress correlated image sources by fully utilizing such correlation. However, in addition to this correlation information, the current symbol of most real image sources is correlated to the preceding or subsequent symbols. Such correlation information should also play an important role for improving the compression performance of channel code-based DSC schemes. To this end, we present an efficient message passing mechanism for LDPC Code-based DSC schemes (ELCDSC) to compress correlated image sources. By utilizing this message passing mechanism, we enable LDPC code-based DSC techniques to not only make full use of the inter-source correlation to assist compression, but also integrate the intra-source correlation in each message passing iteration to improve the compression performance. It is the first that enables LDPC code-based DSC techniques to achieve the utilization of both intra- and inter-source correlations in the message passing mechanism. Experimental results reveal that ELCDSC significantly enhances the compression ratio of correlated image sources, surpassing other DSC schemes.